Perceived Usefulness of Instagram as a Marketing Tool in Higher Education Institutions - Jastini Mohd Jamil; Rusliana Rusle; Mohamad Fadli Zolkipli; Izwan Nizal Mohd Shaharanee (Pejabat Karang Mengarang UPSI, 2021)
Social media marketing, including the use of Instagram, is becoming a prevalent part of the promotional marketing mix by higher education institutions. This study investigates the factors that influence the perceived usefulness of Instagram as a marketing tool in Higher Education Institutions specifically in Community College in Malaysia. An online questionnaire was used to collect data from the 278 semester one community college students in Pahang.  Based on the results, most of the participants were Malay male at the age of 18 years old which were familiar with Instagram and frequently used the application. The results show that there is no difference between gender towards perceived usefulness of social media. The results also indicate that all the hypotheses suggested have been positive and significant. It is worth noting that there were strong connections between hedonic value and co-creation value towards perceived usefulness of social media as the marketing tools in higher education institutions. Additionally, this article contributes practically by providing some guidelines on Instagram advertising.